Advancing the understanding of the PE/PPE protein families through PPE_MPTR protein expression and analysis of pe/ppe single nucleotide variants in differentially drug sensitive Mycobacterium tuberculosis. - Bartizal, Tom Jack (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.